2015
DOI: 10.1371/journal.pone.0141436
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Fibronectin Binding Proteins A and B among Staphylococcus aureus Bloodstream Isolates Are Not Associated with Arthroplasty Infection

Abstract: BackgroundNonsynonymous single nucleotide polymorphisms (SNPs) in fibronectin binding protein A (fnbA) of Staphylococcus aureus are associated with cardiac device infections. However, the role of fnbA SNPs in S. aureus arthroplasty infection is unknown.MethodsBloodstream S. aureus isolates from a derivation cohort of patients at a single U.S. medical center with S. aureus bacteremia (SAB) and prosthetic hip or knee arthroplasties that were infected (PJI, n = 27) or uninfected (PJU, n = 43) underwent sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…While similar observations have been reported in other studies [29], a recent study of prosthetic joint infection with S. aureus found no polymorphic or amino acid sequence differences in the fnbp gene [11]. Here, we found that SNPs in previously described loci including E652D, H782Q, K786N, H818Q, T826N, and S839N were not significantly different between the IE and non-IE groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While similar observations have been reported in other studies [29], a recent study of prosthetic joint infection with S. aureus found no polymorphic or amino acid sequence differences in the fnbp gene [11]. Here, we found that SNPs in previously described loci including E652D, H782Q, K786N, H818Q, T826N, and S839N were not significantly different between the IE and non-IE groups.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that the ability of S. aureus to attach to undamaged endothelial cells could be the key mechanism in S. aureus IE. This observation has led many to speculate that pathogenassociated factors may play more a central role in the development of IE than previously thought [10,11]. Staphylococcus aureus expresses a wide range of virulence factors, including microsomal surface component recognizing adhesive matrix molecule family (MSCRAMM) and numerous secretory toxins [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, a similar role for fibronectin binding was not found for hematogenous PJI in humans (45). To identify potential pathogenic factors that contributed to the hematogenous orthopedic implant infection in our mouse model, we investigated S. aureus AT and ClfA because they are involved in biofilm formation in vitro (35,36) and in human synovial fluid specimens ex vivo (38) and have been implicated in septic arthritis (39, 40) and primary orthopedic implant infections in mice and humans (37,41).…”
Section: Resultsmentioning
confidence: 97%
“…These experiments were performed on the wild-type peptide and each of the double mutant peptides. We focused on the double rather than single mutants because multiple polymorphisms have been linked to disease in humans (12,14,15,47). Supplemental Table S2 shows these k off values for NTD-Fn.…”
Section: Afm-measured Off-rate (K Off ) For Interactions With the N-tmentioning
confidence: 99%